Video Clips to Enhance The Development of The Students’ Speaking Skill - Nurul Afifah; Dewi Lestari (Linguistic, English Education and Art (LEEA) Journal, 2019)
The aimed of this study at investigating how the use of video clips could improve students’ speaking skills of the class VIII D students of SMP NEGERI 1 Madang Suku III OKU TIMUR. This research was categorized into action research and implemented 2 cycles based on the class schedule. The researcher collaborated with the English teacher in this research. The sample of the study was 26 students of class VIII.D. The qualitative data are obtained through observation, interview, and documentation related to the teaching and learning process of speaking in the classroom including the techniques used by the teacher, the learning media and the classroom speaking activities. The findings showed that the use of video clip as the teaching media combined with the use of speaking activities and classroom English was proven to be effective to improve the students’ speaking skills. It means that students’ attention and increased their learning motivation. Through native speakers’ talks, the students got appropriate models and could have better understanding how to use English in real situation so it opened their opportunity to practice speaking. The students who just gained 6.35 in the pre-test were able to increase their score up to 13.65 in the post-test. It indicated that they made a considerable improvement in some aspects of speaking skills such as fluency, pronunciation, grammar, vocabulary, and comprehension. Keywords: enhance, development, video clips, speaking skill, improve